Cold-water immersion alters muscle recruitment and balance of basketball players during vertical jump landing. Issue 4 (16th February 2016) - Macedo, Christiane de Souza Guerino; Vicente, Rafael Chagas; Cesário, Mauricio Donini; Guirro, Rinaldo Roberto de Jesus
Abstract: The purpose of this study was to evaluate the effects of cold-water immersion on the electromyographic (EMG) response of the lower limb and balance during unipodal jump landing. The evaluation comprised 40 individuals (20 basketball players and 20 non-athletes). The EMG response in the lateral gastrocnemius, tibialis anterior, fibular longus, rectus femoris, hamstring and gluteus medius; amplitude and mean speed of the centre of pressure, flight time and ground reaction force (GRF) were analysed. All volunteers remained for 20 min with their ankle immersed in cold-water, and were re-evaluated immediately post and after 10, 20 and 30 min of reheating. The Shapiro–Wilk test, Friedman test and Dunn's post test ( P  < 0.05) were used. The EMG response values decreased for the lateral gastrocnemius, tibialis anterior, fibular longus and rectus femoris of both athletes and non-athletes ( P  < 0.05). The comparison between the groups showed that the EMG response was lower for the athletes. Lower jump flight time and GRF, greater amplitude and mean speed of centre of pressure were predominant in the athletes. Cold-water immersion decreased the EMG activity of the lower limb, flight time and GRF and increased the amplitude and mean speed of centre of pressure.